Pandemic and Language Education: Lessons for Literacy Learning in Elementary School - Liana Mumrikoh; Djono Djono; Nur Arifah Drajati (Journal of International Conference Proceedings, 2022)
Distance learning is presently followed via way of means of instructional establishments global to offer college students with ongoing education for the duration of the COVID-19 pandemic. The impact of the pandemic was felt at all levels of society, including in elementary schools especially in the learning activities. This study aims to determine the use of teaching materials used before and during the pandemic, as well as changes in learning activities in elementary school students. Design of the research is descriptive qualitative research. The data were collected through online questioner, documentation and interviews. Participants in the survey were the teachers of elementary school in Indonesia. Using examples of curriculum changes, student surveys, and exemplary student responses, this study provided departmental scholars with the opportunity to reassess their education system online and offline and renew their role as teachers. The findings were analyzed using a structural equation model. This research contributes as an evaluation material in the learning system during a pandemic so that it can improve the quality of learning both offline and online.Â Keywords: literacy learning, pandemic, elementary school